Analisis Representasi Konsep Ikigai dalam Album Jepang BTS THE BEST oleh BTS (Tinjauan Pendekatan Semiotika Roland Barthes) - Faidah, Rindi; Artadi, Ari; Saptaji, Hargo (DBSMB, Vocational College of Universitas Gadjah Mada, 2025)
Losing Ikigai can happen to young people in finding their purpose in life. Lack of understanding of Ikigai makes it difficult for someone to find Ikigai. So it is very important to prepare Ikigai from a young age. BTS songs are in Japanese, there is a possibility that the implied positive meaning is not clearly conveyed to listeners. The purpose of this study is to explain the definition and concept of Ikigai, the representation of the Ikigai concept contained in the BTS Japanese Album, THE BEST using Roland Barthes' semiotics. The method used is descriptive qualitative approach. The data source was obtained from the reduced BTS song lyrics using Roland Barthes' theory and Ken Mogi's Ikigai theory as research objects. The results of this study are that there are 19 songs in BTS' Japanese album, THE BEST which represent the concept of Ikigai, 4 songs represent the first pillar 'Starting small', 4 songs represent the second pillar 'Releasing oneself', 3 songs represent the third pillar 'Harmony and sustainability', 3 songs represent the fourth pillar 'The joy of little things' and the fifth pillar 'Being in the here and now' represents the most pillars in the Ikigai concept, namely 5 songs.